Influence of lactic-acid bacteria feed supplementation on free amino acid levels in serum and feces of rainbow trout (Oncorhynchus mykiss, Walbaum 1792) - Gabriel R. A. Carneiro; Constanza Opazo; Gustavo Ramalho Cardoso Do Santos; Henrique Marcelo Gualberto Pereira; Gustavo Monnerat; Gustavo Monnerat; Rafael Opazo (Frontiers in Marine Science, 2023)
IntroductionThe influence of intestinal microbiota, particularly lactic-acid bacteria, on digestion and nutrient metabolic activities has been extensively studied. In this research, we investigated the effects of supplementing the feed of rainbow trout (O. mykiss) with P. acidilactici or L. lactis probiotics. A Control group without probiotic supplementation was also included. The study aimed to evaluate growth, feed conversion indices, free amino acid levels in serum and feces, and the relative gene expression of amino acid solute carrier transporters (SLC).MethodsRainbow trout weighing 73.9±10 g were fed with a basal commercial diet supplemented with mono-strains of P. acidilactici or L. lactis at a dosage of 5 x 108 CFU per gram of feed for 60 days. The trout were reared in 100-liter tanks with independent closed recirculation systems, with a water replacement rate of 80% of the total volume daily and a controlled temperature of 15 ± 0.3 °C. The proximate composition of the basal diet consisted of crude protein (49.8%), fat (32.1%), fiber (1.31%), ash (13%), and moisture (8.3%) on a dry matter basis. The diet was provided at a rate of 2% of bodyweight per day.ResultsNo significant differences (p > 0.05) were observed in growth and feed conversion indices between the experimental groups. However, significant differences in free amino acid levels in feces and serum samples (p ≤ 0.05) were observed. The P. acidilactici group exhibited significantly higher levels of glutamate, lysine, proline, and tyrosine in feces samples, and higher levels of arginine, iso/leucine, phenylalanine, proline, serine, threonine, and valine in serum samples compared to the Control group. Additionally, the supplemented probiotic groups showed significant downregulation (p ≤ 0.05) of theslc6a19 and slc7a9 genes, which encode transporters for neutral and cationic amino acids.DiscussionThe autochthonous rainbow trout strain, P. acidilactici, demonstrated more pronounced effects on amino acid levels in feces and serum compared to the non-autochthonous L. lactis strain. However, the increased amino acid levels, particularly in the serum, resulting from P. acidilactici supplementation, did not lead to improved trout growth or feed conversion. Nonetheless, lactic-acid bacteria supplementation induced measurable metabolic effects, as evidenced by elevated levels of specific amino acids in the serum and feces.Future research should focus on evaluating these probiotic effects using specialized diets and considering the observed metabolic effects in this study.